The Relationship between Nutrient Patterns and Bone Mineral Density in Postmenopausal Women - Ilesanmi-Oyelere BL; Brough L; Coad J; Roy N; Kruger MC (MDPI (Basel, Switzerland))
In women, the menopausal transition is characterized by acid-base imbalance, estrogen deficiency and rapid bone loss. Research into nutritional factors that influence bone health is therefore necessary. In this study, the relationship between nutrient patterns and nutrients important for bone health with bone mineral density (BMD) was explored. In this cross-sectional analysis, 101 participants aged between 54 and 81 years were eligible. Body composition and BMD analyses were performed using dual-energy X-ray absorptiometry (DXA). Nutrient data were extracted from a 3-day diet diary (3-DDD) using Foodworks 9 and metabolic equivalent (MET-minutes) was calculated from a self-reported New Zealand physical activity questionnaire (NZPAQ). Significant positive correlations were found between intakes of calcium (p = 0.003, r = 0.294), protein (p = 0.013, r = 0.246), riboflavin (p = 0.020, r = 0.232), niacin equivalent (p = 0.010, r = 0.256) and spine BMD. A nutrient pattern high in riboflavin, phosphorus and calcium was significantly positively correlated with spine (p < 0.05, r = 0.197) and femoral neck BMD (p < 0.05, r = 0.213), while the nutrient pattern high in vitamin E, α-tocopherol, β-carotene and omega 6 fatty acids was negatively correlated with hip (p < 0.05, r = -0.215) and trochanter BMD (p < 0.05, r = -0.251). These findings support the hypothesis that a nutrient pattern high in the intake of vitamin E, α-tocopherol and omega 6 fatty acids appears to be detrimental for bone health in postmenopausal women.
Keywords: nutrient pattern; dietary fat; dietary calcium; bone mineral density; osteoporosis; 0908 Food Sciences; 1111 Nutrition and Dietetics